Original Oil in Place Estimation with an Uncertainty Quantification using Monte Carlo Simulation - ZULVI AMELIA (NIM 12204053), DECI
In field exploration activity there is always an uncertainty factor that appear from the obtaining data. As we know that reserves estimation is the very important aspect in determining Plan of Development activities in one field. With the obtaining exploration data that have the high uncertainty, reserves can be estimated with also the high uncertainty. The objection of this study is to find the way how to estimate initial reserves using the obtaining data from exploitation activity following with the uncertainty quantification based on Monte Carlo simulation result. The exploitation data applied in that reserves estimation method are logging data and geologic and geophysic mapping data. This paper discuss about the reserves estimation application statistically in one field using the obtaining statistical exploitation data. This reserves estimation method is done in one horizon or field prospect (single horizon prospect method). The GGR study has been done before to estimate reserves in this field with volumetric and material balance method. Then the uncertainty quantification from each reserves estimation method would be done by using Monte Carlo simulation result. In this reserves estimation method we use log normal distribution assumption in the scattered exploitation data because there is tendency of data with small value turned up naturally (skewness > 0). Based on this study result it can be concluded that the reserves obtained with single horizon prospect method (statistic) using graphical plotting is 45.65 MMSTB, which is the P73 value in Monte Carlo simulation result. This result indicated the better uncertainty level than the result from the volumetric method that give reserves 51.25 MMSTB, the P75 value. Meanwhile the material balance method put on value 43.98 MMSTB, the P72 value. The material balance result give the best certainty value than the other methods because of the utilizing of production data in calculation process.